(3TQM bUjOI (B" (3HGfJ jYGO (B" (3dcYH Hf RgjQs - (3ceGd GdOjf CHi GdHQcGJ YHO GdQMef Hf eMeO GdCfHGQis; (3RgjQ Hf CHj oSrdnej QHjYI Hf QjGM GdeRfj GdeVQjs
(3ChdgG (B:s
(3bGd GdTjN YHO GdQMef Hf eMeO GdCfHGQi QVi Gddg Yfg (B: (3GdMeO ddg Pi GdLhO hGdcQe hHYO abO TQMJ ai gPg GdChQGb bUjOI cYH Hf RgjQ GdJi eOM HgG GdfHi Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3hVGMjI GdeJfjf eG HQR ddTeS efg Ci dedGSI LdOgG dGjKHJ Ydjg bQGO hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B52 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B186s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdMQe Gdeci (B((3COH (B80) s
Keywords: (3GdCOHs